Sustainable development as a challenge for a society and an economy - Janusz Reichel (Economic and Environmental Studies (E&ES), 2017)
During the political process leading up to the Earth Summit in Rio de Janeiro in 1992 it was decided that the concept which will be used to coordinate spontaneous development processes will be the concept of sustainable development. Since that time, efforts are made to implement this concept through inclusion in the legal regulations and by modelling the development objectives of societies. This process should be accompanied by: 1) a reflection over a direction in which we should go and 2) a question whether actions, carried out in the spirit of sustainable development, really bring us closer to the realisation of this concept. The proposed paper will develop these last two questions focusing on how to get at least a partial response. A proposition of measuring a distance to a sustainable goal(s) for countries is presented.
Keywords: Q01; Q56; O44; 330; sustainable development; GDP; ISEW; HDI; Ecological Footprint